Electrolyte, preparation method thereof, electrochemical device, electrochemical energy storage device, and electric device
Patent Information
- Application Number
- CN202610786959.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-02
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]本申请旨在提供一种电解液及其制备方法、电化学装置、电化学储能装置、用电装置,用于解决硅在嵌锂/脱锂过程中伴随体积膨胀效应,导致负极表面的电解质界面膜在充放电循环过程中反复破裂,从而影响电池的长期循环稳定性及快速充电能力的问题
本申请实施例中,通过在电解液中加入卤代碳酸酯,卤代碳酸酯可优先在硅基负极新鲜裸露界面原位重构、生成稳定负极电解质界面钝化膜,有效隔绝硅基底与电解液直接接触,抑制电解液无序分解消耗,从而提升循环性能;同时,在电解液中引入含氟有机硅烷化合物与草酸型锂盐,含氟有机硅烷化合物可在正极表面构筑致密、超薄且具备高离子电导率的正极电解质界面膜;草酸型锂盐可同时在负极、正极两侧界面同步生成稳定、致密的离子传导界面钝化层,从正负极两端双向优化界面稳定性。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application belongs to the field of new energy technology, specifically relating to an electrolyte and its preparation method, an electrochemical device, an electrochemical energy storage device, and an electrical device. Background Technology
[0002] Batteries, with their advantages of high operating voltage, long cycle life, low self-discharge rate, and environmental friendliness, have become one of the most promising electrochemical energy storage systems, widely used in pure electric vehicles, hybrid electric vehicles, and smart grid energy storage. As end-user applications place higher demands on driving range, there is an urgent need to develop battery systems with higher energy density to effectively alleviate range anxiety in electric vehicles.
[0003] Among the known anode active materials, the development and application of silicon-based anode materials have received widespread attention.
[0004] However, silicon undergoes a volume expansion effect during lithium insertion / extraction, which causes the electrolyte interface film on the negative electrode surface to rupture repeatedly during charge-discharge cycles, thus affecting the battery's long-term cycle stability and fast-charging capability. Summary of the Invention
[0005] This application aims to provide an electrolyte and its preparation method, an electrochemical device, an electrochemical energy storage device, and an electrical device to solve the problem that the volume expansion effect of silicon during lithium insertion / deintercalation causes the electrolyte interface film on the negative electrode surface to rupture repeatedly during charge-discharge cycles, thereby affecting the long-term cycle stability and fast charging capability of the battery.
[0006] To solve the above-mentioned technical problems, this application is implemented as follows: In a first aspect, embodiments of this application provide an electrolyte comprising a halocarbonate, an oxalate-type lithium salt, and a fluorinated organosilane compound.
[0007] In one embodiment, the chemical formula of the fluorinated organosilanes is as shown in Formula I.
[0008] R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.
[0009] In one embodiment, the fluorinated organosilane compound comprises at least one of the following chemical formulas:
[0010] In one embodiment, the oxalate-type lithium salt includes at least one of lithium oxalate borate and lithium oxalate phosphate.
[0011] In one embodiment, the lithium oxalate borate salt includes at least one of lithium dioxalate borate and lithium difluorooxalate borate; and / or, The lithium oxalate phosphate salt includes at least one of lithium difluorooxalate phosphate, lithium tetrafluorooxalate phosphate, and lithium dioxalate phosphate.
[0012] In one embodiment, the halocarbonate includes at least one of fluoroethylene carbonate and difluoroethylene carbonate.
[0013] In one embodiment, based on the mass of the electrolyte, the halogenated carbonate has a% mass percentage of a%, the oxalate-type lithium salt has a% mass percentage of b%, and the fluorinated organosilane compound has a% mass percentage of c%. Wherein, the range of a is 1 ≤ a ≤ 12; and / or, The range of b is 0.01 ≤ b ≤ 1; and / or, The range of c is 0.01≤c≤1.
[0014] In one embodiment, a / (b+c) ranges from 1.3 to 50; and / or, The range of b / c is 0.06 to 5.
[0015] In one embodiment, the electrolyte further includes a non-aqueous solvent and / or a lithium salt; The non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; and / or, The lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.
[0016] Secondly, embodiments of this application provide a method for preparing an electrolyte, the method being applicable to the aforementioned electrolyte, the method comprising: A film-forming additive is obtained by mixing halogenated carbonates, lithium oxalate salts, and fluorinated organosilane compounds. The electrolyte is obtained using the film-forming additive.
[0017] Thirdly, embodiments of this application provide an electrochemical device comprising a positive electrode, a negative electrode, a membrane, and the aforementioned electrolyte, wherein the membrane is disposed between the positive electrode and the negative electrode.
[0018] In one embodiment, at least one of the following conditions is met: The negative electrode includes a negative electrode current collector and a negative electrode active material disposed in the negative electrode current collector, wherein the negative electrode active material includes at least one of silicon-carbon material and carbon-based material; The positive electrode includes a positive electrode current collector and a positive electrode active material disposed in the positive electrode current collector. The positive electrode active material is a layered lithium composite oxide, and the general formula of the layered lithium composite oxide is Li. 1+x Ni y Co z Mn (1-y-z) O2, where -0.1≤x≤0.2; 0.5≤y≤1, 0.05≤z≤0.5.
[0019] Fourthly, embodiments of this application propose an electrochemical energy storage device, which includes the electrochemical device described above.
[0020] Fifthly, embodiments of this application propose an electrical device including the aforementioned electrochemical energy storage device, wherein the electrochemical energy storage device serves as the power supply for the electrical device.
[0021] Compared with the prior art, this application has the following advantages: In this embodiment, by adding halocarbonate to the electrolyte, the halocarbonate can preferentially reconstruct and generate a stable negative electrode electrolyte interface passivation film in situ at the fresh exposed interface of the silicon-based negative electrode, effectively isolating the silicon substrate from direct contact with the electrolyte and inhibiting the disordered decomposition and consumption of the electrolyte, thereby improving cycle performance. At the same time, fluorinated organosilane compounds and oxalate-type lithium salts are introduced into the electrolyte. The fluorinated organosilane compounds can construct a dense, ultrathin positive electrode electrolyte interface film with high ionic conductivity on the positive electrode surface. The oxalate-type lithium salts can simultaneously generate a stable and dense ion-conducting interface passivation layer at both the negative and positive electrode interfaces, thus optimizing the interface stability from both ends of the positive and negative electrodes.
[0022] In summary, by combining halogenated carbonates, fluorinated organosilicon compounds, and oxalate-type lithium salts in the electrolyte, the problem of repeated rupture of the electrolyte interface film on the negative electrode surface during charge-discharge cycles caused by the volume expansion effect of silicon during lithium insertion / deintercalation is effectively solved, thereby reducing interface impedance and improving battery cycle stability and fast charging capability.
[0023] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of this application. Detailed Implementation
[0024] The embodiments of this application will now be described in detail, wherein the same or similar reference numerals denote the same or similar elements or elements having the same or similar functions throughout. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.
[0025] Among currently known anode active materials, silicon (Si) possesses an extremely high theoretical specific capacity (approximately 4200 mAh / g), far exceeding the theoretical specific capacity of traditional commercial graphite anodes (372 mAh / g). Silicon-carbon composite anode materials prepared by incorporating silicon into graphite systems can achieve reversible specific capacities of 400–650 mAh / g. Therefore, the development and application of silicon-based anode materials have attracted widespread attention. However, silicon-based anode materials face significant technical challenges in practical applications: silicon undergoes a volume change of up to approximately 300% during lithium insertion / extraction. This massive volume expansion and contraction causes the electrolyte interphase (SEI) film to repeatedly rupture during charge-discharge cycles, continuously exposing fresh silicon surfaces and reforming the SEI film. This continuously consumes electrolyte, ultimately leading to electrolyte desiccation, a sharp increase in battery internal resistance, and rapid degradation of battery cycle performance.
[0026] To address the volume expansion problem of silicon-based anodes, various improvement strategies have been explored, such as using nano-silicon particles, porous silicon structures, silicon-carbon composite coatings, and functional binders to buffer volume changes and maintain electrode structural integrity. However, these methods still struggle to completely suppress the repeated rupture and regeneration of the SEI film, especially under high areal capacity or rapid charge-discharge conditions, where volume-induced interfacial instability remains a significant issue. Furthermore, some modification methods (such as excessively thick carbon coatings or the addition of excessive inert buffer phases) can significantly increase interfacial impedance and reduce ion diffusion kinetics, thereby sacrificing the battery's fast-charging capability. Therefore, effectively suppressing the volume expansion effect of silicon-based anodes and constructing a stable and low-impedance SEI film interface to improve the battery's long-cycle stability and fast-charging capability remains a critical technical challenge that urgently needs to be addressed in the battery industry.
[0027] To address the aforementioned issues, in a first aspect, embodiments of this application provide an electrolyte comprising a halocarbonate, an oxalate-type lithium salt, and a fluorinated organosilane compound.
[0028] It should be noted that when only halocarbonate is added to the electrolyte, under high-temperature conditions, the halocarbonate is prone to side reactions with lithium salt in the electrolyte, generating corrosive substances such as hydrofluoric acid. Hydrofluoric acid continuously erodes the positive electrode interface structure, inducing numerous side reactions on the positive electrode side, damaging the stability of the positive electrode interface, and simultaneously consuming active lithium ions in the system, resulting in a significant deterioration in the battery's high-temperature cycle performance. Therefore, oxalate-type lithium salts and fluorinated organosilane compounds are also added to the electrolyte to form a complex system, synergistically addressing the problem of deterioration in long-cycle stability and fast-charging capability caused by the volume expansion effect of the silicon-based negative electrode.
[0029] In this embodiment, by adding halocarbonate to the electrolyte, the halocarbonate can preferentially reconstruct and generate a stable negative electrode electrolyte interface passivation film in situ at the fresh exposed interface of the silicon-based negative electrode, effectively isolating the silicon substrate from direct contact with the electrolyte and inhibiting the disordered decomposition and consumption of the electrolyte, thereby improving cycle performance. At the same time, fluorinated organosilane compounds and oxalate-type lithium salts are introduced into the electrolyte. The fluorinated organosilane compounds can construct a dense, ultrathin positive electrode electrolyte interface film with high ionic conductivity on the positive electrode surface. The oxalate-type lithium salts can simultaneously generate a stable and dense ion-conducting interface passivation layer at both the negative and positive electrode interfaces, thus optimizing the interface stability from both ends of the positive and negative electrodes.
[0030] In summary, by combining halogenated carbonates, fluorinated organosilicon compounds, and oxalate-type lithium salts in the electrolyte, the problem of repeated rupture of the electrolyte interface film on the negative electrode surface during charge-discharge cycles caused by the volume expansion effect of silicon during lithium insertion / deintercalation is effectively solved, thereby reducing interface impedance and improving battery cycle stability and fast charging capability.
[0031] Alternatively, in one embodiment, the fluorinated organosilanes have the chemical formula of Formula I.
[0032] R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.
[0033] It should be noted that R1 can be a substituted or unsubstituted group with 1 to 5 carbon atoms, R2 can be a substituted or unsubstituted group with 1 to 5 carbon atoms, and R3 can be a substituted or unsubstituted group with 1 to 5 carbon atoms. The number of carbon atoms can be one of 1, 2, 3, 4, or 5.
[0034] For example, the unsubstituted alkyl group can be at least one of methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, and isopentyl.
[0035] The substituents can be fluorinated; for example, the substituted alkyl group can be at least one of fluoromethyl and fluoroethyl.
[0036] The substituents can be methoxy or ethoxy substituted; for example, the substituted alkyl group can be at least one of methoxymethyl or ethoxyethyl.
[0037] Alkoxy groups can be methoxy, ethoxy, propoxy, isopropoxy, butoxy, isobutoxy, pentylooxy, etc. Alkenyl groups can be vinyl, allyl, 1-butenyl, isobutenyl, pentenyl, etc. Alkynyl groups can be ethynyl, propynyl, butynyl, pentynyl, etc. Aryl groups can be phenyl, etc.
[0038] In the embodiments of this application, the fluorinated organosilane compound molecules have active silicon-fluorine bonds at their end groups. Combined with short-chain alkyl, hydrocarbon, alkoxy and other functional groups, they can preferentially decompose on the positive electrode surface to form a thin and stable positive electrode electrolyte interface (CEI) protective film with excellent ionic conductivity, which blocks the electrolyte from corroding the positive electrode and inhibits positive electrode side reactions. At the same time, it can help optimize the structure of the silicon negative electrode electrolyte interface (SEI) film, enhance the interface flexibility, and adapt to the large volume expansion conditions of silicon negative electrodes. It reduces the dependence on the amount of halocarbonate used, and after being compounded with oxalate-type lithium salt, it achieves synchronous stability of the positive and negative electrode interfaces, and improves the room temperature and high temperature cycle life of high silicon negative electrode batteries.
[0039] Optionally, in one embodiment, the fluorinated organosilane compound includes at least one of the following chemical formulas:
[0040] It should be noted that R1, R2, and R3 in Formulas II, III, and IV are all unsubstituted alkyl groups, and the number of carbon atoms in the alkyl groups of R1, R2, and R3 is less than or equal to 2. For example, the number of carbon atoms can be either 1 or 2.
[0041] Specifically, in chemical formula II, R1, R2, and R3 are all unsubstituted alkyl groups, wherein the alkyl group is methyl and has 1 carbon atom.
[0042] In chemical formula III, R1, R2, and R3 are all unsubstituted alkyl groups, of which R1 and R2 are unsubstituted methyl groups with 1 carbon atom; and R3 is an unsubstituted ethyl group with 2 carbon atoms.
[0043] In chemical formula IV, R1, R2, and R3 are all unsubstituted alkyl groups, wherein the alkyl group is an ethyl group with 2 carbon atoms.
[0044] In the embodiments of this application, the substituent groups of the fluorinated organosilicon are all saturated short-chain alkyl groups. Saturated short-chain alkyl groups have small molecular steric hindrance and excellent electrolyte compatibility, which can fully expose the active silicon-fluorine bonds and rapidly form a film on the electrode surface. The resulting positive and negative electrode interface film has low thickness and excellent ion conductivity. At the same time, it has good high-temperature thermal stability and structural flexibility, which can stabilize the positive electrode CEI film and adapt to the large volume deformation of the silicon negative electrode, continuously maintain the integrity of the negative electrode interface, and effectively improve the high-temperature tolerance and cycle life of the high-silicon negative electrode battery.
[0045] Optionally, in one embodiment, the oxalate-type lithium salt includes at least one of lithium oxalate-borate and lithium oxalate-phosphate. The above-mentioned substances contain oxalate coordination functional groups and boron and phosphorus inorganic framework structures in their molecules, enabling the simultaneous formation of a stable passivation interface film with excellent ionic conductivity at the positive and negative electrode interfaces of the battery. The oxalate ions can effectively chelate hydrofluoric acid and acidic impurities in the system, inhibiting the corrosion and side reactions of electrolyte decomposition products on the positive electrode interface and improving interface stability under high-temperature conditions. Simultaneously, the formed composite interface film exhibits excellent flexibility.
[0046] Optionally, in one embodiment, the lithium oxalate borate salt includes at least one of lithium dioxalate borate and lithium difluorooxalate borate.
[0047] It should be noted that lithium dioxaborate (LiBOB) is rich in dioxacid coordination structure, which has excellent anode film formation performance and can form a passivation film with high flexibility and high structural stability.
[0048] Lithium difluorooxalate borate (LiDFOB) contains fluorine atoms, oxalic acid groups, and a boron framework. It can not only construct a dense and oxidation-resistant CEI film on the positive electrode surface to suppress high-temperature side reactions and transition metal dissolution, but also optimize the interface characteristics of the negative electrode.
[0049] In the embodiments of this application, the above-mentioned substances all contain oxalic acid coordination groups and boron inorganic frameworks, which can chelate acidic corrosive substances such as hydrofluoric acid in the system and reduce the corrosion of the positive electrode interface.
[0050] Optionally, in one embodiment, the lithium oxalate phosphate salt includes at least one of lithium difluorooxalate phosphate, lithium tetrafluorooxalate phosphate, and lithium bis(oxalate) phosphate.
[0051] It should be noted that lithium difluorooxalate phosphate has a moderate amount of fluorine substitution, is suitable for both room temperature and high temperature applications, and is compatible with conventional high-silicon anode systems.
[0052] Lithium tetrafluorooxalate phosphate has the highest fluorine substitution content and is suitable for high-temperature and high-pressure cathode conditions.
[0053] Lithium bis(oxalate) phosphate is a fluorine-free, bis(oxalate) coordination structure with the strongest chelating ability, focusing on improving the cycle of silicon anodes and effectively neutralizing acidic impurities.
[0054] In the embodiments of this application, the above-mentioned substances have good compatibility with fluorinated organosilanes and halogenated carbonates, and at the same time have oxalic acid coordination groups and a rigid inorganic framework of phosphoric acid, which can simultaneously form a stable passivation interface film on the positive and negative electrode surfaces; the oxalic acid groups can effectively chelate acidic corrosion products such as hydrofluoric acid in the system, inhibit positive electrode interface corrosion and side reactions, and alleviate the high-temperature degradation problem caused by halogenated carbonates.
[0055] Optionally, in one embodiment, the halogenated carbonate includes at least one of fluoroethylene carbonate and difluoroethylene carbonate.
[0056] It should be noted that fluoroethylene carbonate (FEC) and difluoroethylene carbonate (DFEC) have cyclic carbonate skeletons and fluorinated functional groups.
[0057] In the embodiments of this application, fluoroethylene carbonate has a moderate cost, strong film-forming stability, and wide applicability, while difluoroethylene carbonate is a difluorinated substitute with a higher fluorine content, resulting in a denser film. Both exhibit high electrochemical reduction activity and can preferentially decompose into a film at the fresh interface of the silicon anode, prior to the solvent of the basic electrolyte. The cyclic structure provides good film density, and the fluorine element imparts corrosion resistance and ion conductivity to the interfacial film. Furthermore, they exhibit excellent compatibility with fluorinated organosilane compounds and oxalate-type lithium salts, with good solubility and dispersibility, no precipitation, and no stratification, making them suitable for existing electrolyte systems.
[0058] Optionally, in one embodiment, the mass percentage of halocarbonate is a% based on the mass of the electrolyte; wherein the range of a is 1≤a≤12.
[0059] For example, the value of 'a' can be one of 1%, 2%, 3%, 5%, 7%, 9%, 10%, 12%, or any two of these values.
[0060] When the halogenated carbonate is fluoroethylene carbonate, its mass percentage content can be one of 2%, 3%, 5%, 8%, 10%, or any two of these values.
[0061] When the halogenated carbonate is difluoroethylene carbonate, its mass percentage content can be one of 1.5%, 2%, 3%, 4%, 5%, or any two of these values.
[0062] When the halogenated carbonate is fluoroethylene carbonate or difluoroethylene carbonate, its mass percentage can be one or any two of the following: 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4%. Among them, when the mass percentage of the halogenated carbonate is 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, and 4%, the corresponding mass percentages of fluoroethylene carbonate and difluoroethylene carbonate in the halogenated carbonate are (0.5%, 0.5%), (0.8%, 0.7%), (1.2%, 0.8%), (1.5%, 1.0%), (1.5%, 1.5%), (2.0%, 1.5%), and (2.2%, 1.8%).
[0063] In this embodiment, the mass percentage of halocarbonate is within the above range, which can ensure that sufficient halocarbonate monomers continuously form a stable fluorine-rich SEI film at the damaged and newly formed interface of the silicon anode, effectively adapting to the large volume deformation during the charging and discharging process of the silicon anode, suppressing excessive decomposition of the electrolyte and irreversible loss of active lithium; avoiding the reaction with lithium salt at high temperature to generate a large amount of hydrofluoric acid, and preventing the corrosion of the positive electrode interface and the aggravation of high-temperature side reactions.
[0064] Optionally, in one embodiment, the mass percentage of oxalate-type lithium salt is b% based on the mass of the electrolyte; wherein b ranges from 0.01 to 1.
[0065] For example, the value of b can be a range of one or both of the following: 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.20%, 0.50%, 0.80%, 1%.
[0066] When lithium oxalate borate is lithium dioxalate borate, its mass percentage content can be one or any two of the following: 0.10%, 0.20%, 0.30%, 0.40%, 0.50%.
[0067] When lithium oxalate borate is lithium difluorooxalate borate, its mass percentage content can be one or any two of the following: 0.08%, 0.10%, 0.20%, 0.30%, 0.40%.
[0068] When lithium oxalate borate salt is lithium dioxalate borate or lithium difluorooxalate borate, its mass percentage content can be any one or any two of the following: 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.20%, and 0.30%. Specifically, when the mass percentage content of lithium oxalate borate salt is 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.20%, and 0.30%, the corresponding mass percentages of lithium dioxalate borate and lithium difluorooxalate borate in the lithium oxalate borate salt are (0.005%, 0.005%), (0.02%, 0.01%), (0.025%, 0.025%), (0.05%, 0.03%), (0.05%, 0.05%), (0.12%, 0.08%), and (0.18%, 0.12%).
[0069] When lithium oxalate phosphate is lithium difluorooxalate phosphate, its mass percentage content can be one or any two of the following: 0.05%, 0.08%, 0.10%, 0.20%, 0.30%, 0.50%, 0.80%.
[0070] When lithium oxalate phosphate is lithium tetrafluorooxalate phosphate, its mass percentage content can be one of 0.15%, 0.20%, 0.4%, 0.50%, 0.55%, or any two of these values.
[0071] When lithium oxalate phosphate is lithium bisoxalate phosphate, its mass percentage content can be one or any two of the following: 0.08%, 0.10%, 0.20%, 0.35%, 0.40%, 0.45%.
[0072] When lithium oxalate phosphate is lithium difluorooxalate phosphate or lithium tetrafluorooxalate phosphate, its mass percentage content can be any one or any two of the following: 0.01%, 0.05%, 0.08%, 0.10%, 0.20%, and 0.40%. Specifically, when the mass percentage content of lithium oxalate phosphate is 0.01%, 0.05%, 0.08%, 0.10%, 0.20%, and 0.40%, the corresponding mass percentages of lithium difluorooxalate phosphate and lithium tetrafluorooxalate phosphate in the lithium oxalate phosphate are (0.005%, 0.005%), (0.03%, 0.02%), (0.05%, 0.03%), (0.05%, 0.05%), (0.13%, 0.07%), and (0.24%, 0.16%).
[0073] When lithium oxalate phosphate is lithium difluorooxalate phosphate and lithium bisoxalate phosphate, its mass percentage content can be one or any two of the following: 0.01%, 0.05%, 0.10%, 0.20%, 0.25%, 0.30%, and 0.35%. Specifically, when the mass percentage content of lithium oxalate phosphate is 0.01%, 0.05%, 0.10%, 0.20%, 0.25%, 0.30%, and 0.35%, the corresponding mass percentages of lithium difluorooxalate phosphate and lithium bisoxalate phosphate in the lithium oxalate phosphate are (0.005%, 0.005%), (0.03%, 0.02%), (0.05%, 0.05%), (0.14%, 0.06%), (0.15%, 0.10%), (0.18%, 0.12%), and (0.20%, 0.15%).
[0074] In this embodiment, the mass percentage of oxalate-type lithium salt is within the above range, which ensures that it has sufficient interface modification and chelation deacidification capabilities, forming a stable auxiliary passivation film on the positive and negative electrode surfaces, inhibiting positive electrode corrosion and side reactions, and preventing problems such as increased electrolyte viscosity, decreased solubility, and excessive decomposition and gas generation.
[0075] Optionally, in one embodiment, the mass percentage of the fluorinated organosilane compound is c% based on the mass of the electrolyte; the range of c is 0.01≤c≤1.
[0076] For example, the value of c can be a range of one or both of the following: 0.01%, 0.03%, 0.05%, 0.08%, 0.10%, 0.20%, 0.50%, 0.80%, 1%.
[0077] When the fluorinated organosilanes are of formula II, their mass percentage content can be any one or any two of the following: 0.10%, 0.15%, 0.20%, 0.30%, 0.40%, 0.50%, and 0.80%.
[0078] When the fluorinated organosilanes are of formula III, their mass percentage content can be any one or any two of the following: 0.01%, 0.05%, 0.08%, 0.10%, 0.15%, 0.20%, 0.30%, 0.40%, and 0.50%.
[0079] When the fluorinated organosilane compound has the chemical formulas II and III, its mass percentage content can be any one or any two of the following: 0.01%, 0.08%, 0.10%, 0.20%, 0.30%, and 0.40%. Among them, when the mass percentage content of the fluorinated organosilane compound is 0.01%, 0.08%, 0.10%, 0.20%, 0.30%, and 0.40%, the corresponding mass percentage contents of formulas II and III in the fluorinated organosilane compound are (0.005%, 0.005%), (0.05%, 0.03%), (0.06%, 0.04%), (0.10%, 0.10%), (0.18%, 0.12%), and (0.20%, 0.20%), respectively.
[0080] In the embodiments of this application, the mass percentage content of the fluorinated organosilanes is within the above range, ensuring that the Si-F active bonds in the molecule can be preferentially adsorbed and oxidized on the positive electrode surface, generating a thin CEI film with high ionic conductivity in situ; avoiding excessive deposition of the positive electrode CEI film and excessive film thickness, and preventing an increase in interface impedance.
[0081] Optionally, in one embodiment, the mass percentage of halocarbonate is a%, the mass percentage of oxalate-type lithium salt is b%, and the mass percentage of fluorinated organosilane compound is c%, based on the mass of the electrolyte; the range of a / (b+c) is 1.3 to 50.
[0082] For example, the value of a / (b+c) can be a range of one or both of the following: 1.3, 1.5, 1.8, 2.0, 5.0, 8.0, 10, 15, 20, 25, 30, 40, 50.
[0083] In this embodiment, when a / (b+c) is within the above-mentioned value range, it can ensure that the halocarbonate is the main body for interface repair, continuously repairing the damaged interface of the silicon anode, forming a stable and flexible SEI film, adapting to the volume expansion of the silicon anode, and ensuring the cycle stability of the anode; the oxalate-type lithium salt and the fluorinated organosilicon compound undertake the auxiliary functions of acid removal, positive electrode passivation, and high temperature stability, with clear distinction between primary and secondary functions and no component antagonism, so that the long-term cycle stability and high temperature tolerance of the battery can reach the optimal balance.
[0084] Optionally, in one embodiment, the mass percentage of oxalate-type lithium salt is b%, and the mass percentage of fluorinated organosilane compound is c%, based on the mass of the electrolyte; the range of b / c is 0.06 to 5.
[0085] For example, the value of b / c can be a range of one or both of the following: 0.06, 0.09, 0.10, 0.15, 0.20, 0.50, 0.80, 1.0, 3.0, and 5.
[0086] In the embodiments of this application, b / c is within the above range, which can ensure that the oxalate-type lithium salt has sufficient chelation and acid removal and dual interface regulation capabilities, and ensure that the fluorinated organosilicon effectively plays the role of positive electrode film formation, high temperature resistance and anti-oxidation, and prevent the oxalate-type lithium salt from causing the interface film to be too thick and the ion conduction to be blocked.
[0087] Optionally, in one embodiment, the electrolyte further includes a non-aqueous solvent; wherein the non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate.
[0088] It should be noted that ethylene carbonate (EC) has high dielectric properties, strong film-forming ability, and high temperature resistance, making it a basic film-forming framework for electrolytes.
[0089] Dimethyl carbonate (DMC) has the lowest viscosity, fast ion conduction, and significant fast-charging gain.
[0090] Ethyl methyl carbonate (EMC) has an asymmetric structure, better thermal stability than DMC, is not easily decomposed at high temperatures, and balances high and low temperature performance.
[0091] In the embodiments of this application, the above-mentioned non-aqueous solvents are all cyclic / chain carbonate non-aqueous solvents, which are the main matrix of the electrolyte. They have excellent compatibility with various functional additives (such as halogenated carbonates, fluorinated organosilicon compounds, oxalate-type lithium salts, etc.), and are used to completely dissolve lithium salts and various functional additives to form a homogeneous and stable liquid phase system, providing a continuous medium for ion migration and conduction.
[0092] Optionally, in one embodiment, the electrolyte further includes a lithium salt; wherein the lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonylate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.
[0093] It should be noted that lithium difluorophosphate (LiPO2F2) preferentially forms films on both the positive and negative electrodes. The dense and low-resistivity interfacial film reduces the interface impedance of the positive electrode, inhibits high-voltage and high-temperature solvent oxidation, and improves high-temperature cycling and gas expansion.
[0094] Lithium bisfluorosulfonyl imide (LiFSI) has high conductivity, low viscosity, and strong dissociation ability, which improves the performance of fast charging at high rates; it is resistant to hydrolysis and has excellent thermal stability, which reduces electrolyte decomposition; it is suitable for high rate systems.
[0095] Lithium tetrafluoroborate (LiBF4) has a boron-fluorine structure, outstanding low-temperature performance, and is suitable for wide-temperature systems.
[0096] Lithium hexafluorophosphate (LiPF6) is the core lithium salt standard for commercial power batteries and energy storage batteries.
[0097] In this embodiment, the lithium salt has a stable anionic structure and high dissociation efficiency, which can reduce electrolyte viscosity and increase lithium ion migration rate. It is highly compatible with halocarbonates, fluorinated organosilicon compounds and oxalate-type lithium salts in the electrolyte, effectively improving electrolyte ionic conductivity, reducing ion transport resistance, and enhancing the battery's high-rate fast charging capability. At the same time, it can synergistically participate in the construction of the positive and negative electrode SEI and CEI composite interface film to generate a stable passivation layer.
[0098] Secondly, this application proposes a method for preparing an electrolyte, applicable to the aforementioned electrolyte, the method comprising: A film-forming additive is obtained by mixing halogenated carbonates, lithium oxalate salts, and fluorinated organosilane compounds. Electrolytes are obtained using film-forming additives.
[0099] It should be noted that the electrolyte preparation process must be carried out under an inert gas atmosphere. This inert gas atmosphere can be nitrogen, argon, or similar gases.
[0100] It should be noted that obtaining an electrolyte based on film-forming additives includes obtaining an electrolyte based on film-forming additives and other necessary solvents for preparing the electrolyte, such as non-aqueous solvents and lithium salts.
[0101] In this embodiment, the above preparation method introduces halocarbonate into the electrolyte to preferentially generate a stable negative electrode electrolyte interface film at the fresh exposed interface of the silicon-based negative electrode, thus isolating the silicon substrate from direct contact with the electrolyte and improving cycle performance. At the same time, fluorinated organosilane compounds are also introduced to construct a dense, ultrathin positive electrode electrolyte interface film with high ionic conductivity on the positive electrode surface. The introduction of oxalate-type lithium salt can simultaneously generate a stable and dense ion-conducting interface passivation layer at both the negative and positive electrode interfaces, optimizing interface stability from both ends of the positive and negative electrodes. In addition, the above preparation method is suitable for the large-scale production of electrolytes, while taking into account both performance and safety.
[0102] Thirdly, this application proposes an electrochemical device comprising a positive electrode, a negative electrode, a diaphragm, and the aforementioned electrolyte, wherein the diaphragm is disposed between the positive electrode and the negative electrode.
[0103] For example, the electrochemical device of this application can be a battery.
[0104] Optionally, in one embodiment, the negative electrode includes a negative electrode current collector and a negative electrode active material disposed in the negative electrode current collector, wherein the negative electrode active material includes at least one of silicon-carbon material and carbon-based material.
[0105] The negative electrode active material includes carbon-based materials, which include graphite, amorphous carbon, and carbon nanomaterials. Graphite includes at least one of natural graphite and artificial graphite. Carbon nanomaterials include at least one of graphene, graphene oxide, carbon nanotubes, and carbon fibers.
[0106] Silicon-carbon materials can be porous carbon, porous carbon frameworks, silicon nanoparticles distributed inside porous carbon frameworks, and amorphous carbon layers coated on the surface of porous carbon frameworks.
[0107] Optionally, in one embodiment, the negative electrode further includes a conductive agent and a binder; the conductive agent includes at least one of conductive graphite, conductive carbon (SP), carbon black, carbon nanotubes, and graphene; the binder includes at least one of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylic acid, sodium alginate, and polyvinylidene fluoride.
[0108] Optionally, in one embodiment, the positive electrode includes a positive electrode current collector and a positive electrode active material disposed in the positive electrode current collector. The positive electrode active material is a layered lithium composite oxide, and the general formula of the layered lithium composite oxide is Li. 1+ x Ni y Co z Mn (1-y-z) O2, where -0.1≤x≤0.2; 0.5≤y≤1, 0.05≤z≤0.5.
[0109] For example, layered lithium composite oxides can be Li 1.05 Ni 0.8 Co 0.1 Mn 0.1 O2 (NCM811), Li 1.03 Ni 0.9 Co 0.05 Mn 0.05 O2, Li 1.10 Ni 0.7 Co 0.15 Mn 0.15 O2, Li 1.2 Ni 0.6 Co 0.2 Mn 0.2 O2.
[0110] Optionally, in one embodiment, the positive electrode further includes a conductive agent and a binder. The conductive agent includes at least one of conductive graphite, conductive carbon black, carbon nanotubes, and graphene. The binder includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), and polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP).
[0111] It should be noted that conductive graphite / conductive carbon black is the basic conductive phase, which has the characteristics of low cost and easy dispersion. It can fill the tiny gaps between the positive electrode active material particles, build a basic conductive network, and ensure the basic conductivity of the electrode.
[0112] Carbon nanotubes / graphene are highly efficient conductive phases with ultra-high electronic conductivity and aspect ratio (carbon nanotubes) / specific surface area (graphene). They can bridge the gaps between large particles of positive electrode active material to construct a three-dimensional continuous high-efficiency conductive network, reduce electrode contact internal resistance, and improve battery rate performance.
[0113] Polyvinylidene fluoride (PVDF, also known as polyvinylidene fluoride) is the mainstream binder for battery cathodes. It has excellent compatibility with cathode active materials and conductive agents, strong adhesion, and good resistance to electrolyte corrosion and electrochemical stability.
[0114] Polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) is based on PVDF and introduces hexafluoropropylene, which improves the flexibility of the binder and the electrolyte absorption, making the electrode easier to be wetted by the electrolyte, shortening the ion diffusion path, and relieving the volume stress of the electrode during cycling, thereby further improving cycle life. It can be applied to high-end, high-cycle batteries.
[0115] In this embodiment, the conductive agent in the positive electrode sheet can construct a three-dimensional continuous electron-ion conductive network between the positive electrode active material particles, reduce the internal resistance of the electrode sheet, improve the transmission efficiency of electrons and ions, and ensure the full release of battery discharge capacity and optimization of rate performance. The binder can firmly bond the positive electrode active material and the conductive agent and tightly combine them with the positive electrode current collector, ensuring the structural integrity, mechanical stability and formability of the positive electrode sheet, offsetting the volume stress of the positive electrode active material particles during charging and discharging, maintaining the long-term stability of the conductive network, and improving the battery cycle life. The conductive agent and the binder work synergistically to ensure high conductivity of the electrode sheet while achieving high structural strength.
[0116] Fourthly, embodiments of this application provide an electrochemical energy storage device, which includes the electrochemical device described above.
[0117] For example, the electrochemical energy storage device of this application can be a battery pack.
[0118] Fifthly, embodiments of this application provide an electrical device including the aforementioned electrochemical energy storage device, wherein the electrochemical energy storage device serves as the power supply for the electrical device.
[0119] For example, the electrical devices in this application include vehicles, smart home appliances, robots, power tools, smart wearable devices, mobile electronic devices (such as mobile phones, computers, tablets), drones, and so on.
[0120] The above-described embodiments of the electrochemical energy storage device and the power consumption device include the aforementioned electrochemical device and can achieve the same technical effect. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the electrochemical device embodiments.
[0121] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application.
[0122] The present application will be described in detail below through embodiments.
[0123] Test method: (1) Cyclic capacity retention test: Place the battery in a constant temperature chamber at 35℃ and let it stand for 30 minutes. First, charge it with a constant current of 2C to 4.25V, then charge it with a constant voltage and current limit to the cutoff current of 0.05C. After charging is completed, let it stand for 5 minutes. Then discharge it with a constant current of 1.0C to the cutoff voltage of 3.0V. Test and record the first discharge capacity, which is denoted as D0.
[0124] After completing the initial capacity calibration, perform long-cycle testing according to the following procedure: 1) Let stand for 5 minutes; 2) Charge at a constant current of 1C to 4.25V, then charge at a constant voltage until the charging current drops to 0.05C; 3) Let stand for 5 minutes; 4) Discharge at a constant current of 1.0C to 3.0V; Repeat steps 1) to 4) for 1000 consecutive cycles. Test and record the discharge capacity of the 1000th cycle, denoted as D1.
[0125] Cyclic capacity retention (%) = D1 / D0 × 100% Wherein, D0 is the initial first discharge capacity after standardized battery testing; D1 is the final discharge capacity after 1000 charge-discharge cycles.
[0126] Example 1 (1) Preparation of positive electrode sheet The positive electrode active material (LiNi) 0.8 Co 0.1 Mn 0.1 Conductive agent (conductive carbon and carbon nanotubes), binder (polyvinylidene fluoride) in a ratio of 96:1:0.5:2.5 (LiNi) 0.8 Co 0.1 Mn 0.1A positive electrode slurry is prepared by mixing conductive carbon, carbon nanotubes, and polyvinylidene fluoride (PVDF) in N-methylpyrrolidone at a mass ratio of 1:1 and stirring until homogeneous. Aluminum foil is used as the positive electrode current collector, and the slurry is coated onto its surface. The foil is dried at 120°C for 1 hour, followed by cold pressing, cutting, and slitting to obtain the positive electrode sheet.
[0127] (2) Preparation of negative electrode sheet A negative electrode active material (artificial graphite and SiC, where SiC accounts for 5% of the mass of the negative electrode active material), a conductive agent (conductive carbon and carbon nanotubes), and a binder (sodium carboxymethyl cellulose, polyacrylic acid, and styrene-butadiene rubber) were mixed in deionized water at a mass ratio of approximately 96.25:1.0:0.05:0.3:1.7:0.7 (artificial graphite and SiC:conductive carbon:carbon nanotubes:sodium carboxymethyl cellulose:polyacrylic acid:styrene-butadiene rubber). The mixture was stirred until homogeneous to obtain a negative electrode slurry. Copper foil was used as the negative electrode current collector. The negative electrode slurry was coated onto the surface of the current collector and dried at 120°C for 1 hour. Subsequently, the foil was cold-pressed, cut, and slit to obtain the negative electrode sheet.
[0128] (3) Preparation of electrolyte Under an argon atmosphere at 10°C, a non-aqueous solvent was added and mixed with ethylene carbonate (EC): ethyl methyl carbonate (EMC): dimethyl carbonate (DMC) in a volume ratio of 30:40:30. Subsequently, 8% of a halocarbonate (fluoroethylene carbonate), 0.3% of an oxalate-type lithium salt (lithium difluorooxalate phosphate), 0.3% of a fluorinated organosilane compound (Formula II), and 12.5% of a lithium salt (lithium hexafluorophosphate LiPF6) were added to obtain the electrolyte.
[0129] (4) Battery preparation A 7-micron thick porous polyethylene film was selected as the membrane substrate. Boehmite ceramic slurry was coated on one side of the polyethylene substrate and dried and cured to form a 2-micron thick boehmite ceramic coating. A PVDF adhesive coating was coated on both sides of the ceramic coating. After drying, rolling and shaping, a composite membrane was obtained.
[0130] The positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to act as a separator. The side coated with boehmite ceramic is aligned with the positive electrode. The electrodes are then stacked, placed in an aluminum-plastic film, dried at 80°C, and then injected with the electrolyte. After vacuum sealing, settling, formation, and shaping, the battery is obtained.
[0131] Example 2 The difference between Example 2 and Example 1 is as follows: In Example 2, the amount of halocarbonate added in step (3) of electrolyte preparation was adjusted to 2%, the amount of oxalate lithium salt added was adjusted to 0.8%, and the amount of fluorinated organosilicon compound added was adjusted to 0.8%.
[0132] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0133] Example 3 The difference between Example 3 and Example 1 is as follows: In Example 3, the amount of halocarbonate added in the preparation of electrolyte in step (3) was adjusted to 10%, the amount of oxalate lithium salt added was adjusted to 0.1%, the fluorinated organosilane compound was adjusted to Formula III, and the amount of fluorinated organosilane compound added was adjusted to 0.1%.
[0134] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0135] Example 4 The difference between Example 4 and Example 1 is as follows: In Example 4, the amount of halogenated carbonate added in the preparation of electrolyte in step (3) was adjusted to 5%, the amount of oxalate-type lithium salt added was adjusted to 0.5%, and the amount of fluorinated organosilicon compound added was adjusted to 0.5%.
[0136] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0137] Example 5 The difference between Example 5 and Example 1 is: In Example 5, the amount of halogenated carbonate added in the preparation of electrolyte in step (3) was adjusted to 5%, the oxalate-type lithium salt was adjusted to lithium dioxalate borate, the amount of oxalate-type lithium salt added was adjusted to 0.5%, and the amount of fluorinated organosilicon compound added was adjusted to 0.5%.
[0138] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0139] Example 6 The difference between Example 6 and Example 1 is: In Example 6, the amount of halocarbonate added in step (3) of electrolyte preparation was adjusted to 5%, the amount of oxalate lithium salt added was adjusted to 0.5%, and the amount of fluorinated organosilicon compound added was adjusted to 0.8%.
[0140] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0141] Example 7 The difference between Example 7 and Example 1 is as follows: In Example 7, the amount of halocarbonate added in the preparation of electrolyte in step (3) was adjusted to 5%, and the amount of fluorinated organosilicon compound added was adjusted to 0.8%.
[0142] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0143] Example 8 The difference between Example 8 and Example 1 is: In Example 8, the amount of halocarbonate added in step (3) of electrolyte preparation was adjusted to 5%, the amount of oxalate lithium salt added was adjusted to 0.1%, and the amount of fluorinated organosilicon compound added was adjusted to 0.8%.
[0144] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0145] Example 9 The difference between Example 9 and Example 1 is as follows: In Example 9, the amount of halocarbonate added in step (3) of electrolyte preparation was adjusted to 5%, the amount of oxalate lithium salt added was adjusted to 0.05%, and the amount of fluorinated organosilicon compound added was adjusted to 0.8%.
[0146] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0147] Example 10 The difference between Example 10 and Example 1 is as follows: In Example 10, the amount of halocarbonate added in step (3) of electrolyte preparation was adjusted to 5%, the amount of oxalate lithium salt added was adjusted to 0.5%, and the amount of fluorinated organosilicon compound added was adjusted to 0.1%.
[0148] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0149] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is as follows: In Comparative Example 1, no oxalate-type lithium salt was added in the preparation of the electrolyte in step (3), and the amount of fluorinated organosilicon compound added was 0.5%.
[0150] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0151] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is as follows: In Comparative Example 2, no oxalate-type lithium salt and fluorinated organosilicon compounds were added during the preparation of the electrolyte in step (3).
[0152] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0153] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is as follows: In Comparative Example 3, no halocarbonate was added during the preparation of the electrolyte in step (3).
[0154] The remaining steps and dosages are the same as in Example 1, and a battery is obtained.
[0155] The batteries obtained in each embodiment and comparative example were subjected to cycle capacity retention tests, and the results are shown in Table 1.
[0156] Table 1
[0157] According to the results in Table 1, the battery cycle performance is better when the value of a / (b+c) is between 1.3 and 50. When the ratio is too high, the oxalate lithium salt and fluorinated organosilicon compounds provide insufficient protection for the interface, while the halocarbonate produces a high content of hydrofluoric acid. Therefore, the positive electrode interface is unstable, and the electrolyte undergoes side reactions at the positive electrode interface, resulting in poor high-temperature cycle performance. When the ratio is too low, the halocarbonate content is too low, which provides insufficient protection for the silicon negative electrode interface, resulting in poor cycle performance.
[0158] By comparing Examples 4 with 6-10, the cycle performance was optimal when the b / c ratio was between 0.1 and 5. When the ratio was too low, the amount of lithium oxalate added was less than that of fluorinated organosilane compound, resulting in lithium oxalate being at a disadvantage in the competition, and fluorinated organosilane compound becoming the main additive, leading to insufficiently dense interfacial film. When the ratio was high, lithium oxalate was dominant, forming a high-resistivity interfacial film, which led to deterioration of cycle performance.
[0159] Comparing the cycle capacity retention rates of the various embodiments and comparative examples, the cycle capacity retention rates of the embodiments are all above 77%, while the cycle capacity retention rates of the comparative examples are less than or equal to 72%. It can be seen that this application effectively solves the problem of volume expansion effect of silicon during lithium insertion / deintercalation and the problem of repeated rupture of the electrolyte interface film on the negative electrode surface during charge and discharge cycles by adding halocarbonate, fluorinated organosilicon compound and oxalate lithium salt to the electrolyte. This reduces the interface impedance and thus improves the cycle stability of the battery.
[0160] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0161] Although embodiments of this application have been shown and described, those skilled in the art will understand that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of this application, the scope of which is defined by the claims and their equivalents.
Claims
1. An electrolyte, characterized in that, The electrolyte includes halogenated carbonates, lithium oxalate salts, and fluorinated organosilicon compounds.
2. The electrolyte according to claim 1, characterized in that, The chemical formula of the fluorinated organosilanes is as shown in Formula I. R1, R2, and R3 independently include substituted or unsubstituted groups having 1 to 5 carbon atoms, and the groups include at least one of alkyl, aryl, alkenyl, alkynyl, and alkoxy groups.
3. The electrolyte according to claim 2, characterized in that, The fluorinated organosilane compound includes at least one of the following chemical formulas. 。 4. The electrolyte according to any one of claims 1-3, characterized in that, The oxalate-type lithium salt includes at least one of lithium oxalate borate and lithium oxalate phosphate.
5. The electrolyte according to claim 4, characterized in that, The lithium oxalate borate salt includes at least one of lithium dioxalate borate and lithium difluorooxalate borate; and / or... The lithium oxalate phosphate salt includes at least one of lithium difluorooxalate phosphate, lithium tetrafluorooxalate phosphate, and lithium dioxalate phosphate.
6. The electrolyte according to any one of claims 1-3, characterized in that, The halogenated carbonates include at least one of fluoroethylene carbonate and difluoroethylene carbonate.
7. The electrolyte according to any one of claims 1-6, characterized in that, Based on the mass of the electrolyte, the mass percentage of the halocarbonate is a%, the mass percentage of the oxalate-type lithium salt is b%, and the mass percentage of the fluorinated organosilane compound is c%. Wherein, the range of a is 1 ≤ a ≤ 12; and / or, The range of b is 0.01 ≤ b ≤ 1; and / or, The range of c is 0.01≤c≤1.
8. The electrolyte according to claim 7, characterized in that, The range of a / (b+c) is 1.3 to 50; and / or, The range of b / c is 0.06 to 5.
9. The electrolyte according to any one of claims 1-8, characterized in that, The electrolyte also includes a non-aqueous solvent and / or lithium salt; The non-aqueous solvent includes at least one of ethylene carbonate, propylene carbonate, methyl ethyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate; and / or, The lithium salt includes at least one of lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium bis(oxalatoborate), lithium bis(pentafluoroethylsulfonyl)imide, lithium tri(trifluoromethanesulfonyl)methyl, lithium hexafluoroantimonyate, lithium hexafluoroarsenate, and lithium hexafluorophosphate.
10. A method for preparing an electrolyte, characterized in that, The preparation method is applicable to the electrolyte according to any one of claims 1 to 9, and the preparation method includes: A film-forming additive is obtained by mixing halogenated carbonates, lithium oxalate salts, and fluorinated organosilane compounds. The electrolyte is obtained using the film-forming additive.
11. An electrochemical device, characterized in that, The electrochemical device includes a positive electrode, a negative electrode, a diaphragm, and an electrolyte as described in any one of claims 1 to 9, wherein the diaphragm is disposed between the positive electrode and the negative electrode.
12. The electrochemical device according to claim 11, characterized in that, At least one of the following conditions must be met: The negative electrode includes a negative electrode current collector and a negative electrode active material disposed in the negative electrode current collector, wherein the negative electrode active material includes at least one of silicon-carbon material and carbon-based material; The positive electrode includes a positive electrode current collector and a positive electrode active material disposed in the positive electrode current collector. The positive electrode active material is a layered lithium composite oxide, and the general formula of the layered lithium composite oxide is Li. 1+x Ni y Co z Mn (1-y-z) O2, where -0.1≤x≤0.2; 0.5≤y≤1, 0.05≤z≤0.
5.
13. An electrochemical energy storage device, characterized in that, The electrochemical energy storage device includes the electrochemical device according to any one of claims 11 to 12.
14. An electrical appliance, characterized in that, The device includes the electrochemical energy storage device as described in claim 13, wherein the electrochemical energy storage device serves as the power supply for the electrical device.
